2022
DOI: 10.3389/fnut.2022.984622
|View full text |Cite
|
Sign up to set email alerts
|

Does the Mediterranean diet reduce the odds of diabetic nephropathy in women? A case–control study

Abstract: BackgroundIn recent decades, the prevalence of chronic diseases such as diabetes is increasing. One of the major complications of diabetes is diabetic nephropathy (DN), so it is important to find a way that can delay or control the onset of DN. Therefore, in this study, we investigated the relationship between the Mediterranean diet (MED) and the odds of DN.MethodsThis case–control study was performed among 210 women (30–65 years) who were referred to the Kowsar Diabetes Clinic in Semnan, Iran. Biochemical var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
1
1
Order By: Relevance
“…We found an inverse association between recommended fruit and vegetable consumption and multimorbidity, regardless of sex. Evidence suggests that high consumption of fruits and vegetables is a protective factor for several NCDs, such as obesity ( 89 ), ischemic stroke ( 90 ), and diabetes ( 91 ), contrary to our findings. This can be explained by the following factors: (i) information on the recommended fruit and vegetable consumption is self-reported in the NHS.…”
Section: Discussioncontrasting
confidence: 99%
“…We found an inverse association between recommended fruit and vegetable consumption and multimorbidity, regardless of sex. Evidence suggests that high consumption of fruits and vegetables is a protective factor for several NCDs, such as obesity ( 89 ), ischemic stroke ( 90 ), and diabetes ( 91 ), contrary to our findings. This can be explained by the following factors: (i) information on the recommended fruit and vegetable consumption is self-reported in the NHS.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies have suggested that there is an inverse association between following a plant-based diet (PBD) and the risk of T2DM and its secondary outcomes. In addition, several high-quality dietary strategies, such as Dietary Approach to Stop Hypertension (DASH), Diet Diversity Score (DDS), and Mediterranean dietary pattern (MDP) containing less processed food and rich in plant-based food are associated with delayed progression of DN (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%